(untitled) (Research, Society and Development, 2022)
Objective: to identify in the literature the interventions used by nursing team to avoid the risk of hypothermia and its main complications, and to evaluate the effectiveness of perioperative skin heating systems. Method: this is a systematic literature review, the following databases LILACS, PUBMED and SCIELO were used for the search, considering the studies contemplated according to the theme, in English, Spanish and Portuguese, published between 2009 to 2021. Results: the review consists of 19 studies, which identify risk factors for hypothermia, skin warming methods and activities performed by nurses to treat hypothermia. Conclusion: hypothermia is a challenge for nurses, who must have both scientific knowledge and clinical practice to better treat hypothermia and avoid possible complications, in addition to having knowledge about heating methods.